Analisis Tingkat Kesejahteraan Petani Padi Sawah Di Kabupaten Aceh Utara - Martina, M; Praza, Riyandhi (LPPM Universitas Malikussaleh - Indonesia, 2018)
Aceh Utara is an area of rice production centres in Aceh Province which has a large contribution in fulfillment food needs of community. Even though, doest guarantee the high level of prosperity of rice farmers in Aceh Utara. The research aims to analyze prosperity level rice farmers in Aceh Utara.The research implemented in Sawang District, Lhoksukon, and Baktiya as an area of rice production centers in Aceh Utara. The sample in this research were 60 farmers who do rice farming and analyzed using quantitative descriptive analysis based on prosperity indicators of farmers namely the level of structure of farmer's household income, structure of household food consumption, performance level of household food security, the level of purchasing power of farmer households, and the development of the farmers' exchange rate. Analysis results from indicators of income strusture, structure of household food consumption, performance level of household food security show that the level of prosperity of farmers is still low while seen from the level of purchasing power of farmer households, and the development of the farmers' exchange rate already well